Α-Ionone attenuates high-fat diet-induced skeletal muscle wasting in mice via activation of cAMP signaling. Issue 2 (8th February 2019) - Tong, Tao; Kim, Minji; Park, Taesun
Abstract : α-Ionone, a naturally occurring flavoring agent, attenuates muscle atrophy in HFD-fed mice via activation of cAMP signaling. Abstract : Skeletal muscle atrophy is a common and debilitating condition that lacks a pharmacological therapy. Our aim was to investigate the potential of α-ionone, a naturally occurring flavoring agent, in preventing muscle atrophy and to delineate the mechanisms involved. We found that α-ionone not only stimulated myogenesis but also attenuated palmitic-acid-induced atrophy of cultured skeletal myotubes, as evidenced by an increased myotube diameter and length, fusion index, and cellular protein content. These beneficial actions of α-ionone were abrogated by cAMP inhibitor. The antiatrophic effects of α-ionone on cultured myotubes were confirmed in a corresponding mouse model. The skeletal muscle mass, muscle protein content, myofiber diameter, and muscle strength were greater in α-ionone-treated mice than in untreated animals fed high-fat diet. Furthermore, α-ionone increased cAMP concentration and enhanced its downstream PKA-CREB signaling in skeletal muscle of mice fed high-fat diet. Thus, α-ionone is a promising agent that may enhance skeletal muscle mass and strength.